PERLINDUNGAN HUKUM PASIEN DALAM PELAYANAN KESEHATAN DIGITAL: TINJAUAN SISTEMATIS TERHADAP REGULASI TELEMEDISIN DI INDONESIA - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
The development of telemedicine in Indonesia has brought significant transformation to digital healthcare services, yet raises concerns about legal protection for patients. This study aims to analyze patient legal protection in digital healthcare services through a systematic review of telemedicine regulations in Indonesia. The research method employed is a literature review with a normative juridical approach, using primary legal materials (Permenkes No. 20 of 2019, UU No. 17 of 2023, UU No. 27 of 2022), secondary materials (journals, books, articles), and tertiary materials as data sources. The results show that Indonesia's telemedicine regulatory framework has provided a legal basis for protecting patient rights, including the right to accurate information, personal data protection, quality service standards, and the right to claim compensation. However, implementation of these regulations still faces challenges such as regulatory fragmentation that has not been fully harmonized, regulatory gaps for direct-to-patient telemedicine, low compliance of commercial platforms, minimal oversight, and insufficient legal literacy. Legal liability in telemedicine encompasses three forms: civil, criminal, and administrative, with dispute resolution mechanisms through litigation and non-litigation pathways. Regulatory harmonization, development of more detailed technical regulations, strengthened oversight, and improved legal literacy are needed to ensure optimal legal protection for patients in Indonesia's telemedicine ecosystem.